Pelatihan Metode Bernyanyi pada Pembelajaran Tajwid di Pojok Bahasa dan Literasi - Dede Amelia Agustin; Solihah Bagus; Usep Setiawan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This research is motivated by the fact that many children at the Reading and Language Literacy Corner are still unable to read the Qur’an properly and correctly in accordance with the rules of tajwid, as well as their limited understanding of Qur’anic recitation principles. If correct Qur’anic reading is not introduced and practiced from an early age, children may encounter difficulties in understanding and applying the rules of tajwid in later stages. Based on this condition, tajwid learning activities were conducted using an engaging, enjoyable, and child-friendly method, namely the singing method. This method was implemented to create an interactive learning atmosphere and to help students remember and understand tajwid materials more effectively. The purpose of this research is to assist children at the Reading and Language Literacy Corner in understanding tajwid, which is often perceived as difficult, and to facilitate the delivery of learning materials so that they can be well received by the students. The results of the study indicate that the application of the singing method increases students’ learning enthusiasm and reduces boredom in tajwid learning, thereby enabling children to better understand proper and correct Qur’anic recitation.